PERCEPTIONS OF ELEMENTARY SPECIAL SCHOOL TEACHERS ON ICT BASED INSTRUCTIONAL MEDIA IN FACILITATING CHILDREN WITH SPECIAL NEEDS IN LEARNING IN MAJALAYA DISCTRICT BANDUNG REGENCY - Sidiq, Zulkifli (Prodi Teknologi Pendidikan, 2015)
Abstract. The efforts to overcome the limitations and services of children with special needs at Elementary Special School (SDLB) level has been carried out up through regular debriefing given to SDLB teachers, especially in designing, developing and utilizing ICT based instructional media. The debriefing was carried out through the process of ICT based instructional media training at district level of Bandung Regency. The analysis of SDLB teachers’ perceptions on the ease of improving services to SDLB children conducted in this study found that the use of ICT based instructional media is highly needed in the learning process. Out of 46 SDLB teachers participating as samples in multimedia workshop, they gave their opinion that training on ICT based instructional media was a positive effort to better improve services to children with special needs. This study recommended that the training could be given in a regular basis in order to improve the competency of SDLB teachers in developing ICT based instructional media.Keywords: instructional media, Information Technology, Elementary Special School, trainingAbstrak. Upaya mengatasai keterbatasan dan pelayanan anak berkebutuhan khusus pada jenjang Sekolah Dasar Luar Biasa (SDLB) telah dilakukan hingga melalui upaya pembekalan secara rutin kepada sejumlah guru SDLB, khususnya dalam mendesian, mengembangkan dan memanfaatkan media pembelajaran Teknologi Informasi (TI). Pembekalan dilakukan melalui proses pelatihan pengembnagan media pembelajaran berbasis TI pada tingkat kecamatan di wilayah Kabupaten Bandung. Dari proses penelitian yang dilakukan terhadap analisis persepsi guru SDLB terhadap kemudahan meningkatkan layanan kepada anak SDLB maka diperoleh data yang menunjukkan bahwa penggunaannya media pembelajaran berbasis (TI) dalam proses pembelajaran dinyatakan sangat dibutuhkan. Dari 46 guru SDLB yang berpartisipasi sebagai sampel penelitian dalam pelatihan multimedia, mereka memberikan pendapatnya bahwa pelatihan tentang media pembelajaran berbasis TI sangat positif terhadap upaya meningkatkan layanan pembelajaran anak berkebutuhan khusus secara lebih baik. Sebagai rekomendasi dari studi ini menunjukkan bahwa kegiatan pelatihan yang dilakukan dapat secara rutin diberikan dalam rangka meningkatkan kompetensi guru SDLB dalam bidang pengembangan media pembelajaran berbasis TI.Kata kunci : Media Pembelajaran , Teknologi Informai, SDLB, Pelatihan.